PENGARUH KUALITAS LAYANAN, HARGA DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN DI HYPERMAT JOGJA CITY MALL - Evi Listiana, 12.05.51.0132 (Students Journal of Economic and Management, 2016)
With so many retail companies in Indonesia, then consumers will be more selective in choosing a shopping center that will be used as a place to buy their needs. The problem in this research is "whether the variable quality of service, price, and beliefs influence on customer satisfaction in Hypermat Jogja City Mall. The purpose of this study was to analyze the effect of variable quality of service, price, confidence in the customer satisfaction in Hypermat Jogja City Mall. The number of samples in this study of 100 respondents, the sampling technique used was accidental sampling in which respondents are consumers who buy in Hypermat Jogja City Mall. Collecting data using questionnaires. The results showed that the variables of service quality positively affects customer satisfaction, price positive effect on customer satisfaction, and trust positively affects customer satisfaction d Hypermat Jogja City Mall. Keywords: Service Quality, Price, Trust and customer satisfaction